Association of Anthropometric Profiles with Triglyceide/High-Density Lipoprotein Ratios in Adult Islamic Boarding School Students - Batubara, Astriana Marta; Tsani, A. Fahmy Arif; Utomo, Astika Widy; Syauqy, Ahmad (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of this study was to analyze the relationship between anthropometric profiles and Triglyceide/High-Density Lipoprotein (TG/HDL-C) ratio in adult Islamic boarding school students. A cross-sectional study was conducted on 83 Islamic boarding school students, aged 19 to 23 years, selected using a consecutive sampling design. Anthropometric measurements consisted of Waist Circumference (WC), Waist-to-Hip Ratio (WHR), and Skinfold Thickness (SFT). There were 45.8% students who had high TG/HDL-C ratio, WC (p<0.001; r=0.379) and WHR (p<0,001; r=0.455). The respondents' waist circumference and waist-to-hip ratio were positively associated with TG/HDL-C ratio.